2018
DOI: 10.3389/fphys.2018.01258
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Improves the Energy Sensing and Glycolipid Metabolism of Blunt Snout Bream Megalobrama amblycephala Fed High-Carbohydrate Diets by Activating the AMPK–SIRT1–PGC-1α Network

Abstract: This study investigated the effects of resveratrol on the growth performance, energy sensing, glycolipid metabolism and glucose and insulin load of blunt snout bream Megalobrama amblycephala fed high-carbohydrate diets. Fish (39.44 ± 0.06 g) were randomly fed three diets: a control diet (30% carbohydrate), a high-carbohydrate diet (HC, 41% carbohydrate), and the HC diet supplemented with 0.04% resveratrol (HCR) for 12 weeks. Fish fed the HC diet had significantly high values of nitrogen and energy retention ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 99 publications
(123 reference statements)
3
26
0
Order By: Relevance
“…AMPK, another key energy metabolic sensor, plays a key role in maintaining cellular energy homeostasis and is activated upon alterations in the cellular AMP/ATP ratio ( 52 ). Previous studies have demonstrated that, upon energy deficiency, AMPK activation may result in increased PGC-1α expression and phosphorylation to modulate the expression of several key players in mitochondrial biogenesis and OXPHOS of fatty acids ( 53 , 54 ) ( Fig. 1 ).…”
Section: Fusion and Gcmentioning
confidence: 99%
“…AMPK, another key energy metabolic sensor, plays a key role in maintaining cellular energy homeostasis and is activated upon alterations in the cellular AMP/ATP ratio ( 52 ). Previous studies have demonstrated that, upon energy deficiency, AMPK activation may result in increased PGC-1α expression and phosphorylation to modulate the expression of several key players in mitochondrial biogenesis and OXPHOS of fatty acids ( 53 , 54 ) ( Fig. 1 ).…”
Section: Fusion and Gcmentioning
confidence: 99%
“…Yan et al has demonstrated that AMPK reduces ROS production through the activation of PGC-1α 21 . In addition, AMPK can indirectly activate SIRT1 by regulating the level of NAD+ 22 , which is an NAD+-dependent protein deacetylase that participates in neuroprotection by reducing oxidative stress. SIRT1 activation reportedly improves mitochondrial function and attenuates brain injury by increasing the level of PGC-1α 23 .…”
Section: Introductionmentioning
confidence: 99%
“…In cattle, the beneficial effects of dietary RES might derive in part by preventing mitochondrial ATP synthesis in tumor cells, thereby inducing apoptosis (Gledhill et al, 2007;Lin et al, 2009) via the Sirt1-PGC1α-PPARα pathway (Milton-Laskibar et al, 2018). However, it has been further confirmed in teleosts through the NAD + /NADH ratio (Zhang et al, 2017), phosphorylation (Shi et al, 2018) and acetylation (Schirmer et al, 2012) in post-transcriptional regulation levels. Though the expression of genes related with mitochondrial dysfunction and ATP synthese activity changed, future studies should be conducted to determine the actual pathways involved.…”
Section: Discussionmentioning
confidence: 99%